Review of mycelium composites and the influence of their microtexture on mechanical properties - Pileckienė, Jolanta; Grubliauskas, Raimondas; Tretjakovas, Jurijus (International Conference “Environmental Engineering”, 2026)
This review article aims to evaluate the application potential of mycelium-based biocomposites and to determine how their microtexture influences key mechanical properties. The objective of the study is to synthesize current scientific knowledge on the relationship between fungal growth characteristics and the resulting material performance. The analysis draws on recent research examining how fungal species, substrate composition, and growth conditions shape microstructural features such as hyphal density, pore distribution, and bonding patterns. These microtexture parameters directly affect compressive strength, elasticity, porosity, and the thermal and acoustic behavior of mycelium composites. The reviewed literature highlights the growing use of mycelium-based materials in construction, packaging, textiles, design, and biomedical applications, emphasizing microtexture as a critical determinant of functionality. The findings indicate that enhanced mycelial growth and optimized microstructural organization can significantly improve mechanical performance, making microtexture control essential for the development of durable and sustainable biocomposites.